Is Concept Appraisal Modulated by Procedural or Declarative Manipulations? - Thorne, Sapphira R.; Smortchkova, Joulia; Quilty-Dunn, Jake; Shea, Nicholas; Hampton, James A. (Frontiers in Psychology, 2022)
A recent study has established that thinkers reliably engage in epistemic appraisals of concepts of natural categories. Here, five studies are reported which investigated the effects of different manipulations of category learning context on appraisal of the concepts learnt. It was predicted that dimensions of concept appraisal could be affected by manipulating either procedural factors (spacing of learning, perceptual fluency) or declarative factors (causal knowledge about categories). While known effects of these manipulations on metacognitive judgements such as category learning judgements and confidence at test were replicated, procedural factors had no reliable effects on the dimensions of concept appraisal. Effects of declarative manipulations on some forms of concept appraisal were observed.